E-Marketing Berbasis Web untuk Memenangkan Persaingan Bisnis - Juniardi Juniardi; Idris Gautama So (Bina Nusantara University, 2012)
PT TL is a company engaged in metal roof manufacturing. This research aims to determine the condition of e-marketing run by PT TL. By knowing the condition of e-marketing running, it will be developed emarketing of web-based in accordance to PT TL. To support the research, this study uses the Porter analysis to see the condition of the company's business environment and combine two methods of analysis, namely: (1) Seven Stages of Internet Marketing that is used for the analysis of the needs for the company and customers to see business opportunities existing and to develop appropriate marketing strategies with corporate goals. (2) Quality Function Deployment (QFD) which is used to design the customer experience in order to get the customer needs to be prioritized and to know what kind of website development according to customer requirements. In this case, it is measured the degree of importance of each website aspect and done a comparison between PT TL’s website with a competitor's website. From the analysis it needs to be designed an e-marketing website developed based on customers’ requirements to outperform similar competitors.